Burden of paraquat poisoning in the department of Antioquia, Colombia (2019)
ABSTRACT: Background Paraquat (PQ) poisoning is a public health problem in many regions of Colombia. This study aimed to estimate the burden of PQ poisoning in the Department of Antioquia, Colombia. Methods Disability-adjusted life year (DALYs) were calculated as the sum of years of life lost (YLL) and years of life lived with disability (YLD) due to paraquat poisoning in Antioquia; a bootstrapped method with 1000 iterations was used to estimate each statistical parameter using the package DALY calculator in R. For this instance, the annual incidence of paraquat poisoning was obtained from the reported surveillance data according to regional Government. Results From 2010 to 2016, 3299 DALYs were estimated in the department of Antioquia for PQ intoxication, with a rate of 53.4 DALYs per 100,000 inhabitants. The majority of the DALYs (2852 DALYs) were generated for men ranging from 15 to 44 years old. Conclusion The rate of DALYs reported here is higher than that reported by all chemical poisonings. Better strategies to regulate and restrict the market of this dangerous products are required in Colombia.